2002
DOI: 10.1143/jjap.41.7119
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric Properties of Spark-Plasma-Sintered (Na0.5K0.5)NbO3–PbTiO3Ceramics

Abstract: Rhombohedrally distorted perovskite BiFeO 3 ­K 0.5 Na 0.5 NbO 3 ceramics with ferroelectricity and ferromagnetism were synthesized by solid-state reaction. The effect of K 0.5 Na 0.5 NbO 3 content on the crystal structure, electrical and magnetic properties of a BiFeO 3 ­K 0.5 Na 0.5 NbO 3 system was examined with a view to achieving multiferroic BiFeO 3-based ceramics. Perovskite BiFeO 3 ­ K 0.5 Na 0.5 NbO 3 single phase was obtained by formation of solid solution with K 0.5 Na 0.5 NbO 3 , whereas pure BiFeO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(76 citation statements)
references
References 1 publication
3
71
1
1
Order By: Relevance
“…1 (1 À y)(Na 0.5 K 0.5 )NbO 3 -yPbTiO 3 (y 0.5). [119] As a general conclusion, the SPS technique allows almost fully dense ceramics to be prepared with largely improved properties; this is mainly attributed to the control of their chemical compositions and microstructures. Obviously, the synthesis method for the powdered precursors and the result morphology of those powders also has a drastic effect on the characteristics of the final ceramic material.…”
Section: High-sensitivity Piezoelectrics Chemically Derived From Pbtiomentioning
confidence: 98%
See 1 more Smart Citation
“…1 (1 À y)(Na 0.5 K 0.5 )NbO 3 -yPbTiO 3 (y 0.5). [119] As a general conclusion, the SPS technique allows almost fully dense ceramics to be prepared with largely improved properties; this is mainly attributed to the control of their chemical compositions and microstructures. Obviously, the synthesis method for the powdered precursors and the result morphology of those powders also has a drastic effect on the characteristics of the final ceramic material.…”
Section: High-sensitivity Piezoelectrics Chemically Derived From Pbtiomentioning
confidence: 98%
“…and Wada et al, who both succeeded in processing dense ceramic -(1 À y)(Na 0.5 K 0.5 )NbO 3 -yPbTiO 3 (y 0.5) and NaNbO 3 , respectively -in order to study their electrical responses. [119,120] One of the more studied solid solutions of this system is Na x K 1Àx NbO 3 , due to the good piezoelectric properties it is expected to have; however, because of its poor sinterability under ambient pressure, research has been devoted to new processing methods. The study by Wang et al, [121] using the SPS method, clearly showed that ceramics with $98% densification can be obtained at temperatures of 1 040-1 100 8C (x ¼ 0.5, 0.6 and 0.7).…”
Section: Alkaline Niobate Lead-free Materialsmentioning
confidence: 99%
“…On the other hand, perovskite ceramics seem to be suitable for actuator and high-power applications due to their relatively high piezoelectricity. Perovskite-type leadfree piezoelectric ceramics have been mainly investigated using KNbO 3 -based, 2-5 K, NaNbO 3 -based [6][7][8][9][10][11][12][13] and Bi, NaTiO 3 -based [14][15][16][17][18][19][20][21][22] ceramics. Bi, NaTiO 3 -based ceramics exhibit a transition from a ferroelectric phase to an antiferroelectric phase at temperatures around 200c C, and their piezoelectricity disappears above these temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of piezoelectric ceramics, sodium potassium niobate ceramics with lead-free piezoelectric material have been investigated as alternative material for PZT-based ceramics [1][2][3][4][5][6][7][8][9][10][11][12][13]. Lead-free ferroelectric materials with perovskite structure have a general formula of ABO 3 .…”
Section: Introductionmentioning
confidence: 99%